Strategic Multi-Stakeholder Collaboration in Drug Trafficking Prevention: The National Narcotics Board of Banyuwangi Regency - Akbara Sanubari; Niko Pahlevi Hentika; Andhika Wahyudiono (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Illicit drug trafficking in the border regency of Banyuwangi, characterised by long coastlines and inter-island ferry routes, systematically undermines social and economic resilience, demonstrating the inadequacy of single-agency law enforcement. This study aims to explore in depth the dynamics of multi-stakeholder partnership that integrates government, private sector, academia, media, and community actors within the BNNK Banyuwangi drug prevention programme. A qualitative single-case study design was adopted, involving semi-structured interviews with twelve key participants, non-participant observation of coordination meetings and outreach activities, and analysis of partnership documents, analysed through reflexive thematic analysis. The analysis identified five reinforcing themes: government policy commitment, private sector resource participation, academic research contribution, digital media amplification, and community volunteer resilience, which collectively form an adaptive prevention ecosystem. The limited number of internal BNNK personnel emerged as a significant structural barrier, mitigated through community-based role substitution and digital campaign strategies. The study concludes that the partnership constitutes a social construction whose resilience rests upon inter-pillar trust and grassroots community empowerment. Practical implications include a replicable conceptual model for institutionalising cross-sector coordination forums and aligning corporate social responsibility with drug prevention in other high-vulnerability archipelagic regions.